Knock-out of vasotocin reduces reproductive success in female zebrafish, Danio rerio - Ramachandran, Divya; Sharma, Kusum; Saxena, Vishal; Nipu, Niepukolie; Rajapaksha, Dinusha C.; Mennigen, Jan A. (Frontiers in Endocrinology, 2023)
The vertebrate nonapeptide vasotocin/vasopressin is evolutionarily highly conserved and acts as neuromodulator and endocrine/paracrine signaling molecule. Circumstantial and mechanistic evidence from pharmacological manipulations of the vasotocin system in several teleost fishes suggest sex-and species-specific reproductive roles of vasotocin. While effects of vasotocin on teleost reproductive physiology involve both courtship behaviours and the regulation of the hypothalamic-pituitary-gonadal (HPG) axes, comprehensive studies investigating behavioural and physiological reproductive consequences of genetic ablation of vasotocin in a genetically tractable fish model, such as the zebrafish, are currently lacking. Here, we report the generation of homozygous CRISPR/Cas9-based vasotocin gene knock-out zebrafish. Breeding pairs of vasotocin knock-out fish produce significantly fewer fertilized eggs per clutch compared to wildtype fish, an effect coincident with reduced female quivering courtship behaviour.Crossbreeding experiments reveal that this reproductive phenotype is entirely female-dependent, as vasotocin-deficient males reproduce normally when paired with female wild-type fish.Histological analyses of vasotocin knock-out ovaries revealed an overall reduction in oocytes and differential distribution of oocyte maturation stages, demonstrating that the reproductive phenotype is linked to oocyte maturation and release. Ovarian hormone quantification and gene expression analysis in mutant fish indicated reduced synthesis of Prostaglandin F2a, a hormone involved in ovarian maturation, egg release and regulation of female courtship behaviour in some cyprinids. However, acute injection of vasotocin did not rescue the female mutant reproductive phenotype, suggesting a contribution of organizational effects of vasotocin. Together, this study provides further support for emerging roles of vasotocin in female teleost reproduction in an important teleost model species.